Population planning in india : Policy issues and research priorities - Bose, Ashish; Desai, P. B. (Delhi : B.R. Publishing corporatio, 1989)
The book makes a modest attempt of reflect the perception of individual scholar and administrators in regard a number of policy issues in the Indian context.
Includes bibliographical references.
Keywords: Population research -- Congresses -- |India.